Miniaturized planar RF integrated filters with good harmonic suppression - Shi, Huamin (2008)
Coplanar waveguide (CPW) Filters have been widely considered as one of key building blocks in exploration of RF and microwave integrated circuits. Due to the CPW uniplanar configuration, many circuit elements such as capacitor, inductor and resonator can be easily built up for innovative design of various printed and integrated filter blocks without needing any external packaged or unpackaged lumped elements.